Undertrusted, Overtrusted, or Just Right? The Fairness of (In)Congruence between Trust Wanted and Trust Received - Baer, Michael D.; Frank, Emma L.; Matta, Fadel K.; Luciano, Margaret M.; Wellman, Ned (Academy of Management Journal, 2021)
The nascent literature on feeling trusted has focused on the notion that it is a benefit to employees and their organizations, with several studies demonstrating a link to improved job performance. It is not surprising, therefore, that the prevailing assumption is that employees will react positively when their supervisors trust them more as opposed to less. Recent research, however, has suggested that the benefits of feeling trusted are accompanied by strains, which some employees may be unwilling to bear. Drawing on seminal theorizing on fairness, we propose that employees will perceive their supervisors as being more mindful of their needs—acting more fairly—when there is a fit between trust wanted and trust received, even when the fit is at low levels of trust. By extension, when trust received exceeds or falls short of an employee’s desire for trust, the employee should perceive the supervisor as less fair. We build a model in which the overall fairness perceptions resulting from the trust wanted–received interplay influence employee performance. Our model is supported by a multisource, three-wave field study and an experiment.